2004
DOI: 10.1111/j.0092-5853.2005.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Going It Alone? Strategic Entry under Mixed Electoral Rules

Abstract: Recent studies on strategic voting and entry in elections that combine plurality or majority and proportional representation (PR) have found candidate placement in single-member district (SMD) races to improve a party's PR performance. The primary implication of the existence of "contamination effects" is that parties have an incentive to nominate candidates in as many single-member districts as possible. Pre-electoral coordination in the majoritarian component of mixed electoral systems, however, is far from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 54 publications
2
38
0
1
Order By: Relevance
“…From the perspective of candidates, dual candidacies provide individual‐level gains from cooperation that involve greater electoral security and additional visibility and status. They thus trigger contamination effects that flow from the list tier to nominal tier considerations (Ferrara and Herron ; Herron and Nishikawa ; Krauss, Nemoto, and Pekkanen ; Manow ). They render individual legislators particularly mindful of collective vote‐seeking needs.…”
Section: The Supplementary Nature Of Geographic Representationmentioning
confidence: 99%
“…From the perspective of candidates, dual candidacies provide individual‐level gains from cooperation that involve greater electoral security and additional visibility and status. They thus trigger contamination effects that flow from the list tier to nominal tier considerations (Ferrara and Herron ; Herron and Nishikawa ; Krauss, Nemoto, and Pekkanen ; Manow ). They render individual legislators particularly mindful of collective vote‐seeking needs.…”
Section: The Supplementary Nature Of Geographic Representationmentioning
confidence: 99%
“… 10 Amorim Neto and Cox 1997; Conaghan 1995; Ferrara and Herron 2005; Golder 2006a; Hicken and Stoll 2011; Samuels 2002; Shugart and Carey 1992. …”
mentioning
confidence: 99%
“…Early work on mixed electoral systems has suggested that the effect of both elements—PR and plurality or majority vote—can be analyzed separately, assuming that mixed systems are not much more than the combination of two distinct mechanisms (for instance Moser 1995, 377; Moser and Scheiner 2004; Reed 1999; Stratmann and Baur 2002). 3 Others have shown interactions between both parts of mixed systems, addressed as contamination (Cox and Schoppa 2002; Ferrara and Herron 2005; Ferrara, Herron, and Nishikawa 2005; Herron and Nishikawa 2001; Rose, Munro, and White 2001, and many others) 4 . Both models expect that mixed systems lead to overall outcomes in between PR and plurality/majority vote.…”
Section: Mixed Electoral Systems and Their Effectsmentioning
confidence: 99%